Issue Information. Issue 2 (7th June 2020) - Unknown
Abstract : Cover : In Knutson and Heemstra (https://doi.org/10.1002/cpch.82 ): (A ) A‐to‐I RNA editing is the result of a site‐selective deamination reaction catalyzed by ADAR enzymes. (B ) A‐to‐I editing alters base pairing properties of the nucleobase, resulting in I:C hydrogen bonding. (C ) Crystal structure of EndoV (PDB 2W35) bound to a single‐stranded DNA substrate (purple) with inosine (red) and a Mg 2+ ion (blue). (D ) EndoV supplemented with Mg 2+ results in cleavage of inosine containing transcripts, while Ca 2+ promotes binding. (E) General concept of immunoprecipitation using E. coli EndoV (eEndoV)—maltose binding protein (MBP) fusion and anti‐MBP magnetic beads.